DEVELOPMENT OF A HIGHLY ACTIVE PHOTOCATALYST BASED ON MESOPOROUS TITANIUM DIOXIDE DOPED WITH ALUMINIUM OXIDE - Lebedeva, I.I.; Sizeneva, I.P.; Kiselkov, D.M. (Perm Federal Research Centre Journal, 2015)
The article reports the main results of the 1st year research project implementation in the framework of the «UMNIK» program.Regularities of synthesis conditions control (temperature, pH, chemical composition of reagents, ratio and concentrations of components, introduction of surfactants and modifiers) were found for the directed variation of the photocatalyst characteristics, namely, phase composition, specific surface area, uniform pore size distribution. A method to obtain photocatalysts based on mesoporous titanium dioxide (TiO2) doped with aluminium oxide (Al2O3) was devised. The method provides formation of a developed porous structure and stabilization of the anatase structure of titanium dioxide.